Estimating Plant-Available Water in the Ap Horizon Using Geospatial Analysis of Field and SSURGO Data. Issue 9 (15th May 2018) - Mikhailova, E. A.; Post, C. J.; Chandler, R. D.; Cole, S. A.; Weaver, J. R.; Zurqani, H. A.; Cope, M. P.; Schlautman, M. A.
ABSTRACT: Soil provides many of the requirements needed for terrestrial plant growth, including an adequate supply of water. Because the proportion of plant roots is usually greatest in the top 10 to 15 cm of soil, the soil moisture content in the Ap horizon is particularly important for plant growth and crop yields. Uncertainties in estimates of plant available water in the Ap horizon (AWAp ) often arise from variabilities in field, laboratory and geospatial data at a farm scale. The objectives of this study were to quantify and compare AWAp estimates across the 147-ha Cornell University Willsboro research farm using four different approaches: a) AWAp calculated from values reported in the SSURGO database for available water capacity (AWC) and Ap thickness for the soil map units (SMUs) present on the farm, b) AWAp estimated from soil texture data reported for the SSURGO SMUs, c) AWAp estimated from soil texture data determined from soil cores taken across the farm that were then averaged within each SMU, and d) spatially interpolating the AWAp values predicted from soil cores across the entire farm irrespective of SMU boundaries. Available water in the Ap horizon varied with soil order in the general trend of Alfisols > Inceptisols > Entisols regardless of the estimation approach used. Field measurement-based estimates of AWAp were lower, in general than the reported SSURGO values and estimates based on reported texture in the SSURGO database. The higher abundance of coarse fragments in the Ap horizon of the soil cores collected on the farm partially explains the lower field measurement-based AWAp estimates. In the SSURGO database, values reported for AWC are frequently obtained from a selected pedon from a "type location" and not from the actual study location. These "type locations" can be located far from study sites and even in different states. Although collecting detailed field data may not always be possible due to the high costs of field and laboratory measurements, it is important to understand the potential benefits and limitations of making field-scale and regional AW estimates using the SSURGO database.